Safety and accuracy of neonatal continuous glucose monitoring - Ohishi, Akira; Ueno, Daizo; Fujita, Tomoka; Segawa, Yuki; Yamamoto, Takuya; Fujisawa, Yasuko; Iijima, Shigeo (Pediatrics International, 2023)
Background Hypoglycemia is a significant problem for all neonates and requires minimally invasive and reliable monitoring. The primary objective of this study was to verify the safety and accuracy of the continuous glucose monitoring (CGM) of full‐term neonates using Freestyle Libre, a flash glucose monitoring (FGM) device. Methods The study was conducted on 20 neonates. Shortly after birth, we placed the FGM sensor on the outside of the neonates' thighs. We scanned the CGM values at 60, 120, 180, and 360 min after birth and simultaneously obtained blood glucose values with plantar capillaries by heel puncture. The neonates wore the sensors for up to 6 h and then they were removed. Results Of the 75 data points to be measured, 65 points (86.7%) were obtained by scan. There was no change in the sensor attachment site in 12 of 18 completed cases in this study but we observed slight induration in four cases (22.2%) and slight redness in one case (5.5%) at the sensor puncture site. A moderate correlation was observed between the CGM and blood glucose values. The CGM values tended to be low at 120, 180, and 360 min after birth, and tended to be high only at 60 min after birth. Conclusions The CGM device was safe to wear on the neonate and the CGM data correlated well with blood glucose levels. There was dissociation between CGM data and blood glucose levels in the acute period soon after birth when the blood glucose levels changed rapidly.